Tolerancia del Sacha Inchi (Plukenetia Volubilis L.), A Nemátodos fitoparásitos del Género Meloydogyne Spp, bajo condiciones de Invernadero en la Estación Experimental Agraria “El Porvenir”- Juan Guerra - Castro Sánchez, Melissa Margarita (2013)
We evaluated 10 accessions of Plukenetia volubilis L. "Sacha Inchi" from the Collection Division of the National Research on Genetic Resources and Biotechnology-SUDIRGEB the Experimental Station "El Porvenir" INIA, with the aim of identifying promising genotypes with higher tolerance to nematode Meloidogyne sp. under greenhouse conditions and to develop a scale to measure damage from Fitoparasíticos. The variables were: Emergency plant, and the Emergence of Cotyledons 1st., 2nd, 3rd. and 4th. pair of true leaves (days after sowing, DAS); Incidence of Meloidogyne sp. samples of root and soil biomass (fresh and dry weight of root and foliage), leaf area and Radicular (cm2), plant height (cm) and stem diameter (cm). The statistical analysis used a completely randomized block design (DBCA) ten treatments with three replicates using 5 experimental units (plants). The tests were conducted under the Subproject "Generation of elite lines of Sacha Inchi (Plukenetia volubilis L.), high productivity, high in omega oils and tolerant tonematodes (Meloidogyne spp.) For cultivation in the Amazon region. The results show that there is no significant difference among the accessions evaluated, presenting no tolerance for any of the accessions to Meloidogyne spp. But accessions PER00409-T7-T10 and showed a performance superior to the other accessions in its growth, which could be a possible mechanism of evasion and the pathogen accessions PER000395 and PER000394 were the most susceptible because of low growth, which could be due to the effect of knot nematodes, which should be corroborated with the accessions evaluated in the final field . The information may increase understanding of the accessions conserved in the Collection of INIA-Experimental Station SUDIRGEB "El Porvenir" and it will be an important tool for future planning and management of germplasm collections and for the development of research in genetic improvement of the species.